Pelatihan Produksi Energi Terbarukan Biochar dan Strategi Pemanfaatannya Sebagai Perbaikan Struktur Tanah Serta Penunjang Keberlanjutan Kebun Gizi Desa Kebonan - Dwi Tiga Putri; Tiara Damayanti; Hilal Rozaq Akbar; Yassir Jatmika (Universitas Negeri Semarang, 2026)
The training on the production of renewable energy biochar and its utilization as a soil structure improvement agent was conducted in Kebonan Village, Boyolali Regency. This activity aimed to address the challenges of climate change and food security by promoting the use of biochar derived from coconut shells to enhance soil quality and support the sustainability of the village's nutrition gardens. Biochar, produced through the pyrolysis of organic waste, has significant potential in improving soil texture, stabilizing pH, and reducing the accumulation of nondecomposable agricultural waste. The training involved members of the village's women’s organization (PKK) and local farmers, who were taught the process of biochar production using a cost-effective soil pit method. The biochar produced was then distributed to each nutrition garden in the village, with guidance provided on its application as a soil amendment. The outcome of this initiative demonstrated the community's increased understanding of biochar production and its benefits, contributing to the sustainable management of agricultural waste and the enhancement of local food production systems.